2020
DOI: 10.17113/ftb.58.03.20.6662
|View full text |Cite
|
Sign up to set email alerts
|

The Mastic Tree (Pistacia lentiscus L.) Leaves as Source of BACs: Effect of Growing Location, Phenological Stage and Extraction Solvent on Phenolic Content

Abstract: Research background. Mastic tree (Pistacia lentiscus L.) of the Anacardiaceae family is an evergreen shrub from Mediterranean countries where it is used in traditional medicine. Analysis of P. lentiscus leaf, stem, fruit and root extracts showed high concentrations of principal groups of secondary metabolites (flavonoids, phenolic acids and tannins), suggesting the plant possesses great biological potential. Therefore, the aim of this research is to evaluate the impact of environmental parameters and the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Similarly, the values for total phenols compounds (11.62 -12.45 mg/g) in A. paniculata leaves reported by Nagajothi et al (2018) were lower compared to our study. Variations in phenolic concentrations depend on specific agro-ecosystem conditions such as temperature, altitude and precipitation (Dragović et al, 2020). Naumann et al (2018) Our study demonstrated that there are no significant effect on total phenols concentration (mg/g) in A. paniculata leaves between two harvesting stages.…”
Section: Phenol Characteristics and Biological Activity Of Tannin In A Paniculata Leaves (Before And After Flowering Phase)mentioning
confidence: 45%
See 2 more Smart Citations
“…Similarly, the values for total phenols compounds (11.62 -12.45 mg/g) in A. paniculata leaves reported by Nagajothi et al (2018) were lower compared to our study. Variations in phenolic concentrations depend on specific agro-ecosystem conditions such as temperature, altitude and precipitation (Dragović et al, 2020). Naumann et al (2018) Our study demonstrated that there are no significant effect on total phenols concentration (mg/g) in A. paniculata leaves between two harvesting stages.…”
Section: Phenol Characteristics and Biological Activity Of Tannin In A Paniculata Leaves (Before And After Flowering Phase)mentioning
confidence: 45%
“…Besides, Ahmed et al (2020) also showed that the content of phenolic compounds was associated with maturity stages in Citrus paradise fruits. The difference in results may be due to the different climatic and environmental conditions, pre-and post-harvest factors such as species and cultivars and technical conditions (storage, drying process, transportation and extraction method) (Dragović et al, 2020;Kamaruzaman et al, 2020;Engin and Mert, 2020).…”
Section: Phenol Characteristics and Biological Activity Of Tannin In A Paniculata Leaves (Before And After Flowering Phase)mentioning
confidence: 99%
See 1 more Smart Citation
“…Plants are exposed to substantial phenological variations, including environmental and seasonal fluctuations over the course of the year [2]. Although the metabolic processes leading to the accumulation of bioactive constituents are basically controlled by genetic makeup, physiological conditions and harvesting time are key essential factors that influence bioactive compounds contents in different organs of medicinal plants [3][4][5]. Great variability in phytochemical composition and quantity could also be attributed to plant geographical origin and edaphic factors [6].…”
Section: Introductionmentioning
confidence: 99%
“…Plants have cells known as circadian clock genes, and thus are able to anticipate seasonal changes and adapt to different growing conditions by regulating the development and accumulation of bioactive compounds in the presence of any external or environmental cues [7]. Relations among the accumulation and storage of secondary plant metabolites due to abiotic stresses have not yet been fully defined, and effects are likely to vary depending on the plant, organ, and type of metabolites [3]. Therefore, it is of great importance from the plant material quality point of view to study relations of growth conditions and chemical composition of edible plants.…”
Section: Introductionmentioning
confidence: 99%